2019
DOI: 10.1101/813519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulation of temporal dynamics of synchronous neural activity in adolescents on autism spectrum

Abstract: Autism spectrum disorder is increasingly understood to be based on atypical signal transfer among multiple interconnected networks in the brain. Relative temporal patterns of neural activity have been shown to underlie both the altered neurophysiology and the altered behaviors in a variety of neurogenic disorders. We assessed brain network dynamics variability in Autism Spectrum Disorders (ASD) using measures of synchronization (phase-locking) strength, and timing of synchronization and desynchronization of ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The observed phenomena are interesting to consider in the context of the experimental results on the temporal patterning of neural synchrony in the brain. Multiple experiments show that moderately synchronized brain activity at rest has a very specific temporal pattern: most of the desynchronizations are very short, lasting for just one cycle of oscillation (Park et al, 2010;Ahn and Rubchinsky, 2013;Ahn et al, 2014;Malaia et al, 2020; see also Introduction). This study suggests that noise may be one of the factors promoting this regime of desynchronization dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed phenomena are interesting to consider in the context of the experimental results on the temporal patterning of neural synchrony in the brain. Multiple experiments show that moderately synchronized brain activity at rest has a very specific temporal pattern: most of the desynchronizations are very short, lasting for just one cycle of oscillation (Park et al, 2010;Ahn and Rubchinsky, 2013;Ahn et al, 2014;Malaia et al, 2020; see also Introduction). This study suggests that noise may be one of the factors promoting this regime of desynchronization dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques revealed that neural synchrony in the brain shows a very specific patterning: it is interrupted by potentially numerous but very short desynchronization episodes. This was observed in different species (rodents, humans), different brain signals (spikes, LFPs, EEG), different brain areas (cortex, hippocampus, basal ganglia), and different brain states (healthy and diseased), see (Park et al, 2010;Ahn and Rubchinsky, 2013;Ahn et al, 2014;Ratnadurai-Giridharan et al, 2016;Malaia et al, 2020) for the different experiments. The distribution of desynchronization durations is altered under different conditions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This phenomenon was observed in the synchrony between local field potentials (LFPs) and spikes in different parts of the basal ganglia and EEG in Parkinson's disease (Park et al, 2010;Ratnadurai-Giridharan et al, 2016;Ahn et al, 2018), in synchronization between LFPs recorded in the prefrontal cortex and hippocampus of normal and amphetamine-sensitized mice (Ahn et al, 2014), in EEG of healthy human subjects (Ahn and Rubchinsky, 2013), and in EEG in autism spectrum disorders (Malaria et al, 2020). The differences in the temporal patterning are correlated with certain behavioral features but the prevalence of short desynchronizations persisted nevertheless (Ahn et al, 2014(Ahn et al, , 2018Malaia et al, 2020). Therefore, short desynchronizations may be functionally important and the properties and mechanisms of desynchronization durations merit exploration.…”
Section: Introductionmentioning
confidence: 99%
“…According to Liu [5], the frequency of autistic children's brain waves shows a decrease in both their functional complexity and synchrony with the brain development. Studies carried out in [6][7][8] observed that there were noticeable differences found between the right and the central side of brain areas. Previous studies have shown that there is a relationship between autistic and non-autistic brain EEG signals [9][10][11][12][13].…”
mentioning
confidence: 99%